CORROSION PROTECTION OF POWER LINE AND BRIDGE SUPPORTS - Мелентьєв, Олег (SWorldJournal, 2026)
The article addresses the problem of corrosion damage to metal supports of power transmission lines and bridge structures, which is one of the main causes of reduced operational reliability. The main corrosion mechanisms are analyzed, modern methods of an